2001
DOI: 10.1016/s0042-6989(00)00322-9
|View full text |Cite
|
Sign up to set email alerts
|

Fixation disparity and accommodation for stimuli closer and more distant than oculomotor tonic positions

Abstract: Both the vergence and the accommodative system have individual tonic positions (also referred to as dark vergence and dark focus, respectively) where the static response may be expected to be most accurate. This was confirmed by measuring fixation disparity with nonius lines and accommodation with an autorefractometer for foveal stimuli at viewing distances of 460, 100, 60, 40, and 30 cm. Multiple regression analysis was used at each viewing distance to predict fixation disparity from dark vergence, dark focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 23 publications
7
41
1
Order By: Relevance
“…We assume that fixation disparity measures are physiologically plausible if they are correlated with dark vergence (at least at a viewing distance of 100 cm, which is close to the population mean of dark vergence). Like in a previous study, 29 we found that subjects tended to have an eso or exo fixation disparity if the viewing distance corresponding to dark vergence was closer or more distant than the test distance of fixation disparity (100 cm). This correlation with dark vergence was observed at all gaps with continuous nonius lines and at 1.0-and 3.3-deg gaps with flashed nonius lines.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We assume that fixation disparity measures are physiologically plausible if they are correlated with dark vergence (at least at a viewing distance of 100 cm, which is close to the population mean of dark vergence). Like in a previous study, 29 we found that subjects tended to have an eso or exo fixation disparity if the viewing distance corresponding to dark vergence was closer or more distant than the test distance of fixation disparity (100 cm). This correlation with dark vergence was observed at all gaps with continuous nonius lines and at 1.0-and 3.3-deg gaps with flashed nonius lines.…”
Section: Discussionsupporting
confidence: 85%
“…28 The individual nonius bias can amount to a few minutes of arc (if nonius lines have a vertical gap) and may be a more appropriate reference of fixation disparity than the physical coincidence of nonius lines. 29 Thus, our analyses also include the corrected fixation disparity, i.e., the fixation disparity minus nonius bias.…”
mentioning
confidence: 99%
“…By contrast, when watching the moon high in an empty sky in the relative absence of contextual information, the vergence system will remain in resting posture (right panel of Figure 3). As a result, the eyes will be severely overconverged, resulting in larger fixation disparity (Jaschinski, 2001;Jaschinski et al, 1998).…”
Section: Kimmentioning
confidence: 99%
“…However, the more the accommodative response exceeds the dark focus level (A > DF), the larger the influence of accommodative vergence and-as a result-the more the dissociated phoria is shifted to a closer (i.e., more eso) position; the amount of this accommodative effect depends on the individual AC/A-ratio. Multiple regression analyses have shown that this model is able to explain about 50% of the inter-individual variability of the distant dissociated phoria (Owens & Tyrrell, 1992) and about 80% of the near dissociated phoria (Jaschinski, 2001).…”
Section: Dark Vergence Vs Dissociated Phoriamentioning
confidence: 99%